SOĞUTMA HIZI ETKİLERİNE GÖRE ŞEKİL HAFIZALI BİR CuZnAl ALAŞIMIN X-IŞINI DİFRAKSİYONU İLE MONOKLİ-NİK DİSTORSİYON PARAMETRELERİNİN İNCELENMESİ - Eskil, Murat; Kayalı, Nejdet (Fırat University, 2006)
Austenitik fazdan M18R martensitik faza dönüşüm gösteren bakır bazlı şekil hatırlamalı alaşımlar için ideal sıkı paket yapıyı göstermesi açısından monoklinik distorsiyon parametresi (s) çok önemlidir[1]. CuZnAl alaşımları dönüşümden önce ve sonra uygulanan termal etkilere çok duyarlıdırlar, ve bu etkiler alaşımların kristalografik, morfolojik ve mekanik özelliklerinde önemli değişikliklere yol açabilir. Bu çalışmada farklı termal işlemlerin etkilerine bağlı olarak şekil hafızalı bir CuZnAl alaşımın monoklinik distorsiyon parametreleri X-ışını difraksiyonu kullanılarak hesaplandı.

Monoclinic distortion parameter (s) is important for Copper-based shape memory alloys which transforms from austenitic phase to M18R martensitic phase because the value of s shows the ideally close packed structure[1]. CuZnAl alloys are very sensitive to the thermal effects before and after the transformation, and this effects may cause important changes on crystallographic, morphologic and mechanical properties or the other transformation parameters of the alloys. In this study, the changes which occured on monoclinic distortion parameters of a shape memory CuZnAl alloy due to the effects of various thermal procedures have been calculated by using X-ray diffraction measurements.
INVESTIGATION OF MONOCLINIC DISTORTION PARAMETERS OF A SHAPE MEMORY CuZnAl ALLOY BY MEANS OF X - RAY DIFRACTION DUE TO THE COOLING RATE EFFECT